Pharmacologically active microcarriers delivering BDNF within a hydrogel: Novel strategy for human bone marrow-derived stem cells neural/neuronal differentiation guidance and therapeutic secretome enhancement. (February 2017) - Kandalam, Saikrishna; Sindji, Laurence; Delcroix, Gaëtan J.-R.; Violet, Fabien; Garric, Xavier; André, Emilie M.; Schiller, Paul C.; Venier-Julienne, Marie-Claire; des Rieux, Anne; Guicheux, Jérôme; Montero-Menei, Claudia N.
Graphical abstract: Abstract: Stem cells combined with biodegradable injectable scaffolds releasing growth factors hold great promises in regenerative medicine, particularly in the treatment of neurological disorders. We here integrated human marrow-isolated adult multilineage-inducible (MIAMI) stem cells and pharmacologically active microcarriers (PAMs) into an injectable non-toxic silanized-hydroxypropyl methylcellulose (Si-HPMC) hydrogel. The goal is to obtain an injectable non-toxic cell and growth factor delivery device. It should direct the survival and/or neuronal differentiation of the grafted cells, to safely transplant them in the central nervous system, and enhance their tissue repair properties. A model protein was used to optimize the nanoprecipitation conditions of the neuroprotective brain-derived neurotrophic factor (BDNF). BDNF nanoprecipitate was encapsulated in fibronectin-coated (FN) PAMs and the in vitro release profile evaluated. It showed a prolonged, bi-phasic, release of bioactive BDNF, without burst effect. We demonstrated that PAMs and the Si-HPMC hydrogel increased the expression of neural/neuronal differentiation markers of MIAMI cells after 1 week. Moreover, the 3D environment (PAMs or hydrogel) increased MIAMI cells secretion of growth factors (b-NGF, SCF, HGF, LIF, PlGF-1, SDF-1α, VEGF-A & D) and chemokines (MIP-1α & β, RANTES, IL-8). These results show that PAMs delivering BDNF combined with Si-HPMC hydrogel represent a useful novel local delivery tool in the context of neurological disorders. It not only provides neuroprotective BDNF but also bone marrow-derived stem cells that benefit from that environment by displaying neural commitment and an improved neuroprotective/reparative secretome. It provides preliminary evidence of a promising pro-angiogenic, neuroprotective and axonal growth-promoting device for the nervous system. Statement of Significance: Combinatorial tissue engineering strategies for the central nervous system are scarce. We developed and characterized a novel injectable non-toxic stem cell and protein delivery system providing regenerative cues for central nervous system disorders. BDNF, a neurotrophic factor with a wide-range effect, was nanoprecipitated to maintain its structure and released in a sustained manner from novel polymeric microcarriers. The combinatorial 3D support, provided by fibronectin-microcarriers and the hydrogel, to the mesenchymal stem cells guided the cells towards a neuronal differentiation and enhanced their tissue repair properties by promoting growth factors and cytokine secretion. The long-term release of physiological doses of bioactive BDNF, combined to the enhanced secretion of tissue repair factors from the stem cells, constitute a promising therapeutic approach.